PI3K Inhibition in Combination with Tamoxifen in Patients with Metastatic HR+/HER2- Breast Cancer: Clinical and Circulating Tumor DNA Results. - Voorthuis, Rosie AB; Oliveira, Mafalda; van Rossum, Annelot GJ; de Boo, Leonora W; Mandjes, Ingrid AM; Saura, Cristina; Muñoz, Susana; López García, Dario; Schrier, Mariette; Sikorska, Karolina; Lopez-Yurda, Marta; Schot, Margaret; et al. (American Association for Cancer Research (AACR), 2026)
PURPOSE: To determine the safety and efficacy of taselisib, a selective PI3K inhibitor, in combination with tamoxifen. PATIENTS AND METHODS: POSEIDON is a phase II, randomized, placebo-controlled trial conducted from June 2016 to March 2020. Eligible patients were refractory upon prior endocrine therapy. Prior treatment with cyclin-dependent kinase 4/6 (CDK4/6) inhibitors and everolimus was allowed. Patients were randomized (1:1) to receive either taselisib (4 mg) + tamoxifen (20 mg) or placebo + tamoxifen. The primary endpoint of the trial was investigator-assessed progression-free survival (PFS) in the intention-to-treat (ITT) population (two-sided α 0.2, 90% power). Exploratory biomarker analysis with regards to prognosis and treatment resistance was conducted in circulating tumor (ct)DNA. RESULTS: POSEIDON met its primary endpoint, in which patients treated with taselisib + tamoxifen had improved PFS compared with patients treated with placebo + tamoxifen in the ITT population (median PFS 4.8 months vs. 3.2 months; stratified hazard ratio 0.69; 80% confidence interval, 0.49-0.98, P = 0.17). However, toxicity of taselisib was significant, with diarrhea (40% any grade) as the most common adverse event. Exploratory analyses indicated that high tumor fraction (TF) determined in ctDNA at baseline is associated with worse PFS and overall survival (P < 0.0001). CONCLUSIONS: Our findings suggest efficacy of PI3K inhibition + tamoxifen beyond second-line treatment and after prior targeted therapies, including CDK4/6 inhibition in metastatic HR+/HER2- breast cancer, although the magnitude of benefit did not outweigh the tolerability of this combination. Exploratory biomarker analysis indicates that TF determined in ctDNA differentiates patients based on prognosis and may help optimize patient selection for targeted treatment strategies.
Keywords: Humans; Female; Tamoxifen; Breast Neoplasms; Circulating Tumor DNA; Middle Aged; Antineoplastic Combined Chemotherapy Protocols; Erb-b2 Receptor Tyrosine Kinases; Phosphoinositide-3 Kinase Inhibitors; Aged; Adult; Biomarkers, Tumor; Receptors, Progesterone; Receptors, Estrogen; Prognosis; Phosphatidylinositol 3-Kinases; Imidazoles; Oxazepines